2021
DOI: 10.4314/ahs.v21i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of HIV-TB co-infection among HIV patients: a retrospective Study

Abstract: Background: TB/HIV co-infection is a major public health problem in many parts of the world. But the prevalence of co-infection was varies among countries. This study was designed to assess prevalence of TB/HIV co-infection and to determine its factors. Methods: A retrospective study was done among HIV-positive patients at Hiwot Fana hospital from December, 2014 to 2018. The study participants were selected by simple random sampling. Patients with incomplete chart reviews were exclud- ed and demographic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
10
12
1
Order By: Relevance
“…This report was in agreement with study conducted in the Ethiopia that reported history of TB contact [20] and duration of cough greater than 3 weeks were risk factors of TB [43].…”
Section: Discussionsupporting
confidence: 92%
“…This report was in agreement with study conducted in the Ethiopia that reported history of TB contact [20] and duration of cough greater than 3 weeks were risk factors of TB [43].…”
Section: Discussionsupporting
confidence: 92%
“…The nding of 29% burden of TB/HIV co-infection in the two counties is largely comparable with previously pooled estimates across countries in Sub-Saharan Africa [31]. The prevalence was 31% in Tanzania [32], 27.7%, in Amhara region, 37.4% in Addis Ababa and 36.9% in Southern Ethiopia respectively [33], while in Uganda it was 49.2% [34]. The variation in these estimates across the studies could possibly be explained by the differences in study time, sample size, study settings, methods of diagnosis and the ability to systematically screen HIV on all TB patients.…”
Section: Discussionsupporting
confidence: 85%
“…Viral load at 6 months in both the groups did not differ We observed that the TB infection rate was 4.8% among group A patients, whereas in group B the rate of TB infection was 6.6%. The prevalence rate of TB and HIV coinfection was reported in previous studies as 37.4% by Zeru 27 which was in concordance with 36.9% reported by Negussie et al 28 Kibret et al 29 reported a prevalence rate of 33% while 35.6% was reported by Mbithi et al 30 However, Mitku et al 31 have reported a 27.7% prevalence rate. These differences in the TB and HIV co-infection rate may be because of differences in the study design, study population, study protocol or immune status etc.…”
Section: Discussionsupporting
confidence: 81%